2012
DOI: 10.1126/science.1215418
|View full text |Cite
|
Sign up to set email alerts
|

The Alarmin Interleukin-33 Drives Protective Antiviral CD8 + T Cell Responses

Abstract: Pathogen-associated molecular patterns decisively influence antiviral immune responses, whereas the contribution of endogenous signals of tissue damage, also known as damage-associated molecular patterns or alarmins, remains ill defined. We show that interleukin-33 (IL-33), an alarmin released from necrotic cells, is necessary for potent CD8(+) T cell (CTL) responses to replicating, prototypic RNA and DNA viruses in mice. IL-33 signaled through its receptor on activated CTLs, enhanced clonal expansion in a CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
417
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(459 citation statements)
references
References 40 publications
30
417
2
10
Order By: Relevance
“…Although we found that the levels of total CD3 + CD8 + T cells were similar in the two strains of mice post CVB5 infection, we showed that in the absence of T1/ST2, there was a significant reduction in the number of IFNg-and TNF-a-producing CD3 + CD8 + T cells, which have been implicated in a range of antiviral activities (33,34). This is consistent with a recent report indicating that IL-33 could drive protective antiviral CD8 + T cell responses during LCMV infection in mice (35). NK cells were also thought to be important in controlling CVB5 infection (36).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although we found that the levels of total CD3 + CD8 + T cells were similar in the two strains of mice post CVB5 infection, we showed that in the absence of T1/ST2, there was a significant reduction in the number of IFNg-and TNF-a-producing CD3 + CD8 + T cells, which have been implicated in a range of antiviral activities (33,34). This is consistent with a recent report indicating that IL-33 could drive protective antiviral CD8 + T cell responses during LCMV infection in mice (35). NK cells were also thought to be important in controlling CVB5 infection (36).…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, the Stat6-mediated increase in M2 macrophages and Tregs is likely to depend on mast cells, whereas the Stat6-mediated induction of multifunctional CD8 + T cells and viral clearance is mast cell independent. Therefore, it is possible that IL-33 may act directly on CD8 + T cells as previously shown in an LCMV model (35).…”
Section: Discussionmentioning
confidence: 99%
“…The function of IL-33 induced by P. gingivalis during the development of periodontal diseases remains unknown. Recently, other investigators reported that IL-33 plays an important role for DC-mediated CD8 + cytotoxic T lymphocyte responses (3,6). In our study, fimbriae and PGTP2 promoted DC-meingly, gingival epithelial cells express low levels of TLR2 (19), and IL-33 induction by gingipains is dependent on PAR-2 signaling in gingival epithelial cells.…”
Section: Discussion the Expression Of Il-33 Increases In Response Tosupporting
confidence: 49%
“…Viral, bacterial, fungal, and parasitic infections can each produce a unique inflammatory environment. For instance, lymphocytic choriomeningitis virus (LCMV) infection triggers IFNα and IFNβ production (5), in addition to IL-1, IL-6, IL-10, IL-15, IL-21, IL-33, and TRAIL (6). Furthermore, LCMV-specific T cells readily produce IFNγ, TNFα, IL-2, and CD40L following stimulation with viral peptide antigen (7).…”
mentioning
confidence: 99%